Beneficial Effect of β-Mannanase Feed Enzyme on Performance of Chicks Challenged with Eimeria sp. and Clostridium perfringens - Jackson, M.E; Anderson, D.M; Hsiao, H.Y; Mathis, G.F; Fodge, D.W (Avian diseases, 2003)
Two experiments were conducted to determine the effect of a β-mannanase feed enzyme on the performance of broiler chicks subject to a necrotic enteritis disease challenge model involving oral inoculation of Eimeria sp. and Clostridium perfringens. β-Mannanase is known to improve productive performance when added to poultry and swine diets. In both experiments, disease challenge in the absence of feed additives demonstrated significant reductions in performance as measured by weight gain, feed conversion, and the incidence of coccidial lesion scores. Significant mortality was also observed in challenged groups in Experiment 1. The disease challenge model was therefore judged as highly effective. Additions of a commonly used antibiotic, bacitracin methylene disalicilate (BMD), and coccidiostat, salinomycin, were highly effective in partially counteracting negative effects of the disease challenge. In both experiments, addition of β-mannanase significantly improved performance and reduced lesion scores in disease-challenged groups. The degree of improvement was somewhat less than that afforded by a combination of BMD and salinomycin in Experiment 1 but was not different from that afforded by BMD alone in Experiment 2. We conclude that the β-mannanase enzyme can play a role in circumstances where the use of antibiotics is not desired.